2013
DOI: 10.1164/rccm.201206-1037oc
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Histones Are Mediators of Trauma-associated Lung Injury

Abstract: Rationale: Acute lung injury is a common complication after severe trauma, which predisposes patients to multiple organ failure. This syndrome largely accounts for the late mortality that arises and despite many theories, the pathological mechanism is not fully understood. Discovery of histone-induced toxicity in mice presents a new dimension for elucidating the underlying pathophysiology. Objectives: To investigate the pathological roles of circulating histones in trauma-induced lung injury. Methods: Circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
731
11
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(789 citation statements)
references
References 47 publications
40
731
11
7
Order By: Relevance
“…Infusion of intravenous histones into mice causes sepsis, thrombosis, and death (11). The concentration of histones in the blood reaches 20 M under pathological conditions (43) and is sufficient to saturate prothrombin and promote autoactivation leading to thrombin generation within few hours. Pro-longed exposure to histone H4 is equivalent to a slow infusion of small amounts of thrombin in the circulation, which eventually culminates in prothrombotic and proinflammatory effects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of intravenous histones into mice causes sepsis, thrombosis, and death (11). The concentration of histones in the blood reaches 20 M under pathological conditions (43) and is sufficient to saturate prothrombin and promote autoactivation leading to thrombin generation within few hours. Pro-longed exposure to histone H4 is equivalent to a slow infusion of small amounts of thrombin in the circulation, which eventually culminates in prothrombotic and proinflammatory effects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular injury mediated by extracellular histones has been described experimentally or in human disease of the lung,94 heart,95 liver,96 kidney31 and vascular endothelium 62. Table 2 details the effects of extracellular histones observed in specific cell types.…”
Section: Molecular Basis Of Histone‐related Cellular and Tissue Injurymentioning
confidence: 99%
“…29 The extracellular signal-regulated kinases (ERKs) and p38 MAPK are two major classes of MAPKs that play important roles in transducing inflammatory signals. 30,31 To determine whether these two pathways are involved in the upregulation of IL-6 and IL-8 in ARPE-19 cells, we examined the activation of signaling molecules by western blotting with phospho-specific antibodies. The results showed that ERKs, p38 MAPK, and JNK were all phosphorylated by the histones (Figure 5a).…”
Section: Induction Of Il-8 By Histones Is Mediated By Erk1/2-and P38mentioning
confidence: 99%